He expectations of accounting students’ occupation areas: case study in a University Center of Rio Grande do Sul (Revista Brasileira de Contabilidade e Gestão, 2019)
The Accounting Sciences Graduation Course in Brazil has been gaining more space for several factors. In that way line up the expectations of students with the needs of job market is fundamental for the success of these institutions. This study intends to investigate the Accounting students’ expectations of a university in the north coast of Rio Grande do Sul about the job market, evaluating your pretensions of occupation area after graduation. It was realized a quantitative and descriptive study, using a questionnaire applied to the Accounting students, with questions about the personal features and areas which desired to act in the beginning of the graduation and nowadays. The obtained answers were put in the statistical program SPSS (Statistical Package for the Social Sciences) to use the tool Crosstab Table, and then analyze if the personal features affect in the choice of occupation area. It was concluded as results that the gender, age or semester don’t affect in the occupation area, and the public accounting and general accounting were the most chosen areas between the interviewed, besides that in the beginning of the graduation the students don’t know about the occupations areas of Accounting.
Keywords: Expectations; Areas of Expertise; Accounting; University Graduate